VD_FINDINFO AI 397/19 - 157/2020 vom 1. Mai 2020 - VD Tribunal cantonal (2020)
DÉCISION INCIDENTE, DEMANDE DE PRESTATION D'ASSURANCE, RETRAITVOIE DE DROIT, ASSUREUR, ENFANT, DOMMAGE | 276 CC, 46 LASV, 23 LPGA, 85bis RAI